Sexual Life Style Variables and Risk of Cancer - Tkeshelashvili, Vasil (Caucasus Journal of Health Sciences and Public Health, 2018)
Based on the selective interviews of 5,300 women living in Tbilisi in 1987-1989, peculiarities of menstrual, reproductive and sexual functions have been evaluated with the use of epidemiological questionnaire containing 100 questions and a general picture on the spread of risk factors among the general women population in terms of age, nationality and social status was obtained. Women in Tbilisi mainly (50%) began their sexual life in the age of 19-27. There was a tendency of decrease in the number of women who started sexual life after the age of 28 and slight increase of the number of young women who start sexual life before age of 18. More than half of women (59.6%) have had an irregular sexual life. Its irregularity and absence for 10 and more years have been reported, respectively, in 17.2% and 8.9% of women. Frequency of the latter indicators increased with age. Majority of women (77.8%) reported that they had only one sexual partner in their lives. Only 7.0% reported that they had two and more sexual partners. Proceeding from the confidentiality of this intimate issue, the latter figures, presumably, do not reflect the reality. Women often left the question unanswered. Frequency of two or more sexual partners in life has culminated in all ethnic groups of women with the increase of age. Most women have denied the history of sexually transmitted diseases (STDs). At the same time, the incidence of inflammatory diseases of genital organs (31.1%), including chronic adnexitis (28.0%), were cumulated in late reproductive (352 cases per 1000 women) and premenopausal (359%0) age periods. According to socio-ethnic groups, the highest peak levels of inflammatory diseases of the genital organs were recorded in women of Russian nationalities (492%0) and service field employed females (457%0) living in industrial districts of Tbilisi.